Coordination Modes of Para-Substituted Benzoates Towards Divalent Copper Centers in the Presence of Diimines - Eirini Frantzana; Ioannis Loukas; Antonios G. Hatzidimitriou; Demetrios Tzimopoulos; Pericles Akrivos (Inorganics)
The coordination modes of several para-substituted benzoates towards a copper(II) center is investigated in the presence of α-diimines. The coordination environment of the metal ion also includes nitrogen atoms from 1,10-phenanthroline (phen) or 2,2′-bipyridine (bipy) and, occasionally, oxygen atoms from coordinated water, ethanol molecules or nitrate ions. The compounds are investigated by visible and infrared spectroscopy and by single crystal X-ray diffraction. Although the reaction scheme involved equimolar amounts of the reactants, compounds with metal-to-benzoate-to-diimine ratios of 1:2:1, 1:1:2 and 1:1:1 are realized, being either neutral or cationic in nature and either mono- or dinuclear. The better coordinating ability of nitrate relative to perchlorate is verified, as well as the subtle role of the para-substituent on the coordination mode of the benzoate and consequently on the overall structure of the compounds formed.